Introducing additional factors for the Brazilian market in the fama-french five-factor asset pricing model - Lagnado, Leonardo Mathiazzi (2016)
This dissertation is aimed at evaluating the risk-return relationship of stocks by incrementing the Fama and French five-factor model (F. FAMA and R. FRENCH, 2015) with two new variables. This was done by creating a six-factor model aimed at capturing the size, value, profitability, investment and governance patterns in average stock returns. An additional seven-factor model was also created by adding a herding factor. Governance and herding were chosen as additional factors because of a hypothesis that they would be relevant in less efficient markets such as Brazil. The evaluation of the two model´s performance versus the traditional five-factor model was performed next, as well as the assessment of relevance of the newly added factors. Testing the six-factor model, it had a similar performance to the five-factor model, and the governance factor proved to be relevant in the Brazilian market. Adding the herding factor weakened the results, although the factor still proved to be relevant in some cases.